Housewives' Preferences Using Melon Gas Cylinders: Analytic Hierarchy Process (AHP) Approach - Sukamdani, Hariyadi B.; Satrio, Nugroho Budi; Sukwika, Tatan; Sulistyadi, Yohanes; Eddyono, Fauziah (The Graduate School of Sahid University, 2024)
This study aims to analyze the preferences of homemakers when choosing the type of melon gas cylinder using the Analytic Hierarchy Process (AHP) method. The problem addressed is determining the factors that most influence homemakers' decisions in choosing between subsidized and non-subsidized gas. This research employs a quantitative method with AHP to analyze homemakers' preferences when selecting melon gas cylinders. AHP breaks down complex problems into a simple hierarchical structure, facilitating priority determination. The study involves homemakers chosen through purposive sampling. Data were collected through questionnaires covering relevant criteria and sub-criteria, using a Likert scale to measure the importance of each criterion. The research results based on dynamic sensitivity analysis show that price is the most important factor, followed by ease of use. This study provides a clear picture of the relative weights of various criteria and alternatives when choosing melon gas cylinders. The study's conclusion indicates that homemakers prefer subsidized gas over non-subsidized gas.